Investigating the relatıon between educatıon level and fertılıty in woman 15-45 years old (Case Study Of Shoushtar Cıty)" - Shahmansouri, Kobra; Afshani, Seyyed Alireza (The Turkish Online Journal of Design Art and Communication, 2016)
This study was aimed to investigate the relation between education level and fertility in women 15-45 years old of Shoushtar city. Theoretical principles were used based on their themes in different theory of diffusion and cultural backwardness, Davis and Blake’s theories, the theory of social promotion, economic-social theories, cultural views theories and modernization theory related to this field. Methodology in this research was survey and statistical population of this research was all women 15045 years old in Shoushtar city. And 247 of them have been chosen as a sample and they were studied and it was the study tool. Tool validating was conducted by content and for reliability assessing; Cronbach’s alpha coefficient was used[1]. To data analysis, a statistical software SPSS was used and due to the measurement levels, the methods of descriptive statistics such as frequency tables, charts and in inferential statistic, Pearson tests and Spearman and T were used. Results also showed that there is a significant relation between independent variables included the education level of men and women, women’s employment, income, number of children, attitude to the child, family power structure and religious orientation to the dependent variable of fertility.
Keywords: Fertility; Education; Fertility; Attitude to the Child; Family Power Structure; Doğurganlık; Eğitim; Çocuk Tutum; Aile Güç Yapısı